Hydroxy acid-functionalized ionic liquids as green alternatives for carbonate synthesis from carbon dioxide and epoxide: catalytic and kinetic investigation - Yue, Shuang; Wang, Xuejuan; Wu, Yuee; Zhang, Sining (New journal of chemistry, 2025)
The rising level of atmospheric carbon dioxide (CO 2 ) has become an important factor threatening environments and human health, so development of feasible methods for converting CO 2 into high-value-added chemicals stands out as a hot subject. In this study, an environmentally friendly catalytic system, which consists of a novel hydroxyl acid ionic liquid was successfully prepared for the cycloaddition reaction of CO 2 and epoxides under mild conditions without solvent or co-catalyst. The different reaction variables that affect the cycloaddition reaction were also explored and discussed, including temperature, pressure, time, and amount of catalyst. Under designed reaction conditions, these hydroxyl acid-functionalized ionic liquids exhibited excellent catalytic activity towards various terminal epoxides, in which >99% selectivity of the corresponding cyclic carbonates was achieved. Meanwhile, the catalyst can be recycled at least six times without significant loss of its activity and selectivity. In addition, the reaction kinetics were studied, and the activation energy was determined to be 48.55 kJ mol −1 . Finally, a possible reaction mechanism was proposed, in which the synergistic effects involving the hydroxyl group on the cation and the COO − in functionalized ionic liquids guarantee the reaction to proceeds effectively. An environmentally friendly synthesis route of carbonates from CO 2 and epoxides catalysed by novel hydroxy acid ionic liquids under metal/halogen/cocatalyst/solvent-free conditions.